Corneal neovascularization: a modern view of molecular mechanisms and methods of therapy - G. S. Arzhimatova; E. A. Salikhov; M. Y. Shemyakin (Российский офтальмологический журнал)
This review provides a detailed summary of the issues of etiology, pathogenesis and molecular mechanisms of corneal neovascularization. Signaling molecules involved in the process of neovasculogenesis, as well as their antagonists, antiangiogenic factors, are described. The role of signaling proteins VEGF, MMP and their receptors as modern targets of therapy is described on the basis of a series of clinical studies. The potentials of gene and bioengineering therapy as a promising method of treating corneal neovascularization are presented.